EFEKTIVITAS KERJA TIM PENILAI HARGA TANAH PADA KEGIATAN PELEBARAN JALAN MASUK MENUJU BANDAR UDARA KASIGUNCU KABUPATEN POSO - Labiro, Yus Hastari (Katalogis, 2015)
The purpose ofthis studyis to determine the effectiveness of Appraisal Team Land On Widening activities to wards Airport Road at Kasiguncu Poso districtand the obstacles during this project.This research located at the District Kasiguncu Kab. Poso, Central Sulawesi. The informant as much ass people chosen by purposive sampling. The Data collection by interview, observation and documentation. Technique analyze data through data reduction, data display, anddraw conclusions. The results shows that the Land Appraisal Team have worked well. Based on thein dicator of the ability to adjust, each member of the Appraisal Team Land canadapt well in the team's own internalenvir on mentand the communities thatare directly related to land acquisition activities high way to Kasiguncu Airport. Woke cooperation and good communication among teams, and community leader skey to the success of reaching every stage of land acquisition. The constraintsen countered the suitability of the price of land compensation with local financial capacityand the absence of Appraisal team under the decreeof the Ministerof Finance who will be expected to work objective lybased on the mandate of Ac tNo. 2of 2012 on land acquisition for public purposes.